IMPLEMENTING ICT INTO LANGUAGE AND LAW CLASSROOM TO DEVELOP LAW STUDENTS’ COMMUNICATIVE COMPETENCE - Юлія Василівна Юлінецька; Оксана Юріївна Бабій; Ірина Василівна Гловюк; Андрій Сергійович Степаненко; Микола Іванович Пашковський (Інформаційні технології і засоби навчання, 2021)
The new context of changes in labour-market requirements calls for development of foreign language communication competence and use of technologies that promote professional life-long learning. Individual characteristics necessary for a professional to integrate into the international socio-cultural environment have recently been challenged particularly because of growing demands to the ability to communicate, be autonomous and responsible for the achieved learning outcomes. A switch of the European higher education content to the competence-based learning contributes to the development of the mentioned characteristics and competence. Further, the National Qualifications Framework of Ukraine (7 Level, Second cycle (Master)) envisages mastering foreign language communicative competence in professional activities. This research addresses the issue of ICT tools application in the development of foreign language communicative competence of law students during individual study. We focus on blended learning model, which is combination of traditional and distance learning approaches. To conduct the research, focus groups were defined and examined; relevant authentic material (the VOTA, HUDOC database, and CURIA case-law database) analysed; and the most appropriate ICT tools established. The department of foreign languages of the National University "Odessa Academy of Law" designed, tested, piloted and uploaded the on-line dictionary "gLAWssary"; developed and recorded the video course "Legal English in Use" which is offered on the university website. The results indicate that the on-line dictionary and video course supplemented by the workbook are powerful tools to promote professional life-long learning and that individual study skills are central to this task. This finding suggests that a thoroughly elaborated course with the relevant ICT tools could be the basis for building foreign language communicative competence of future lawyers.